The role of magnetic resonance imaging in the diagnosis of bilateral laryngocele - Ebbi Donald Robinson; Chidinma Wekhe (Wolters Kluwer Medknow Publications, 2020)
Laryngocele is a rare anomalous air-filled dilatation of the saccule of the larynx with unclear etiology. The patient in our case presented with a complaint of a painless anterior neck swelling which moved and increased in size on coughing, swallowing, and straining. Physical examination revealed a compressible swelling measuring approximately 2 cm in the widest diameter in the anterior aspect of the neck with normal overlying skin. It was nontender, soft, cystic, fluctuant, and mobile. The advent of magnetic resonance imaging (MRI) has made its diagnosis easier than the use of laryngoscope. The finding revealed multiple, nonenhancing, oval-shaped but lobulated masses in both infrahyoid visceral spaces involving the paraglottic space with an extralaryngeal component. They hypo to isointense on T1-weighted and hyperintense on T2-weighted and short tau inversion recovery images and measured 3.71 cm × 3.06 cm in the right and 1.27 cm × 1.04 cm in the left (right bigger than left). Hence, a diagnosis of bilateral laryngocele was made. In the index report, MRI being a noninvasive imaging modality using radiofrequency with brilliant soft-tissue contrast and spatial resolution was used to diagnose the lesion. The paucity of literature and information with regard to bilateral laryngocele in our environment and the role of MRI have informed this report.